Initial Evidence for Symptoms of Postpartum Parent-Infant Relationship Obsessive Compulsive Disorder (PI-ROCD) and Associated Risk for Perturbed Maternal Behavior and Infant Social Disengagement From Mother - Ratzoni, Nathalie; Doron, Guy; Frenkel, Tahl I. (Frontiers in Psychiatry, 2021)
Infant socioemotional development and underlying brain maturation occur primarily within the context of early caregiver-infant relationships. Perinatal research demonstrates detrimental impact of postpartum pathology, including postnatal onset of maternal OCD—on the mother-infant relationship. The present study is the first to examine postnatal onset of a particular dimension of OCD symptoms focusing on close interpersonal relationships (relationship-OCD, i.e., ROCD) within a general population sample. Specifically, we assessed whether symptoms of Parent-Child ROCD (PC-ROCD), may onset postnatally, thus yielding symptoms of Parent-Infant ROCD (PI-ROCD). We adapted the previously validated Parent-Child ROCD measure for use during infancy to assess symptoms of PI-ROCD. The adapted measure, Parent-Infant Relationship Obsessive Compulsive Symptoms Inventory (PI-PROCSI), was administered to 143 mothers from the general population at 4-months postpartum. We investigated concurrent associations between postnatal onset of PI-ROCD, maternal depression and bonding, as well as longitudinal predictive associations with observed maternal and infant behaviors in dyadic interactions at 10 months. Due to dropout across the 1st year postpartum, the subsample with longitudinal data was substantially reduced compared to the full sample. PI-PROCSI scores explained unique variance in concurrent maternal depression over and above concurrent anxiety. PI-PROCSI scores also associated with concurrent impairments of maternal bonding. Moreover, unique associations emerged between maternal PI-ROCD scores and perturbations in both maternal and infant observable behaviors at 10-months. Specifically, observable perturbations in maternal behaviors mediated associations between symptoms of PI-ROCD at 4-months and observable infant avoidance of social engagement behaviors at 10-months. Findings suggest that parent-child ROCD symptoms may onset during the postnatal period, and that such symptoms may play a significant role in shaping quality of reciprocal caregiver-infant interactions. Theoretical and clinical implications are discussed.